Peran financial distress Altman memediasi kinerja keuangan terhadap harga saham pada BUMN di BEI - Mia Laksmiwati; Sugeng Priyanto (Penerbit Goodwood, 2021)
Purpose: Testing the effect of financial performance consisting of CR, DER, ROA, TATO on stock prices with Financial Distress as the mediating variable. Research methodology: The data are secondary data in the form of financial reports. This research method uses Path Analysis, and to analyze the data using the SPSS version 25 program. Sample of 16 companies listed on the BEI in 2014-2018. Results: CR, ROA affect FD while DER, TATO do not affect FD. Only TATO has a direct effect on stock prices. FD with the Altman Z score method only indicates the DER. Limitations: The historical data used is limited, 5-year time series and the variables: six variables and Altman Z Score method. Contribution: Non-bank SOEs pay attention to CR, DER and ROA that have not influenced share prices and maintain the performance of TATO. SOE must conduct FD analysis, which is an early warning system, solutions can be found immediately if predicted will experience financial difficulties in the future. Keywords: Financial performance, Financial distress, Stock price